2021
DOI: 10.48550/arxiv.2109.10984
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The dynamics of the TRAPPIST-1 system in the context of its formation

Shuo Huang,
Chris W. Ormel

Abstract: TRAPPIST-1 is an 0.09 𝑀 star, which harbours a system of seven Earth-sized planets. Two main features stand out: (i) all planets have similar radii, masses, and compositions; and (ii) all planets are in resonance. Previous works have outlined a pebble-driven formation scenario where planets of similar composition form sequentially at the H 2 O snowline (∼0.1 au for this low-mass star). It was hypothesized that the subsequent formation and migration led to the current resonant configuration. Here, we investiga… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 81 publications
(151 reference statements)
0
15
0
Order By: Relevance
“…As a different formation model, Ormel et al (2017) proposed that planets grow near the water snowline (r < 1 au), mainly by pebble accretion. In this model, the average planetary mass (Schoonenberg et al 2019) and resonant relation (Lin et al 2021;Huang & Ormel 2021) could be reproduced. In contrast, the mass was determined by the pebble isolation mass; therefore, the planetary mass was almost uniform in the system.…”
Section: Planetmentioning
confidence: 87%
See 2 more Smart Citations
“…As a different formation model, Ormel et al (2017) proposed that planets grow near the water snowline (r < 1 au), mainly by pebble accretion. In this model, the average planetary mass (Schoonenberg et al 2019) and resonant relation (Lin et al 2021;Huang & Ormel 2021) could be reproduced. In contrast, the mass was determined by the pebble isolation mass; therefore, the planetary mass was almost uniform in the system.…”
Section: Planetmentioning
confidence: 87%
“…The TRAPPIST-1 system is characterized by resonant relations. Previous studies (e.g., Coleman et al 2019;Lin et al 2021;Huang & Ormel 2021) investigated how the resonant relations are reproduced. Although this study does not focus on reproducing the resonance relations, we also investigated whether the period ratio agrees with that of the TRAPPIST-1 system.…”
Section: Mean-motion Resonancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a configuration is stable on very long timescales, as opposed to the early N-body simulations by Gillon et al (2017) which typically showed instability on a timescale of 0.5 Myr. Finally Papaloizou et al (2018, see also Brasser et al 2019Huang & Ormel 2021) studied the migration and tidal evolution of the system, arguing that the planets may have migrated in two distinct groups, re-assembling later on, thanks to outward migration of the inner planets driven by tidal interactions with the central star.…”
Section: Introductionmentioning
confidence: 98%
“…Using formation models based either on pebble accretion or planetesimal accretion, several studies have shown that resonant chains such as the one seen in TRAPPIST-1 ⋆ E-mail: jean.teyssandier@unamur.be can naturally arise during the early stages of formation and migration in a disc (Ormel et al 2017;Schoonenberg et al 2019;Coleman et al 2019;Huang & Ormel 2021). As noted by Coleman et al (2019), the majority of pairs end up in first-order resonances (mainly the 2:1, 3:2 and 4:3 MMRs), with a few in second-order resonance (such as the 5:3 MMR which is relevant for this work), but no pair ends up in third-order resonance (which may be relevant for TRAPPIST-1 since the inner pair has a period ratio of ∼ 1.6, and therefore lies near the 8:5 MMR).…”
Section: Introductionmentioning
confidence: 99%